A non-syndromic bifid tongue associated with geographic tongue. - Jerkovic Gulin, S.; Chiriac, A. (European Journal of Pediatric Dermatology, 2017)
A bifid tongue (cleft tongue) is mostly linked to various syndromes associated with different oro-facial-digital abnormalities. A non-syndromic bifid tongue and bifid tongue without association with oro-facial-digital syndromes are very rare. We present a case of non-syndromic bifid tongue associated with ectopic migratory glossitis (geographic tongue) in a healthy 5-year-old child.